2014
DOI: 10.1002/2013ja019497
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of monoenergetic and broadband auroral electron precipitation as observed by the Science and Technology Satellite‐I

Abstract: Previously, the pitch angle distribution of monoenergetic and broadband electron precipitation has been investigated mainly by case studies. The main focus of this study is quantitative comparison of pitch angle distributions between monoenergetic and broadband electron precipitations using long-term observations on board one platform. From December 2003 to October 2004, Science and Technology Satellite-I (altitude∼680 km) regularly observed auroral electron flux and cold ambient plasma parameters during quiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Based on the Cluster observations, Sadeghi et al (2011) reported the characteristics found in the energytime (E-t) spectrograms and field-aligned current distributions obtained in neighboring potential structures. Park et al (2014) also showed similar properties of monoenergetic and broadband auroral electron components observed by the Science and Technology Satellite-I in addition to their electron energy distributions and statistical results on the basic parameters (characteristic energy, energy flux, pitch angle, temperature, and density) and spatial (invariant latitude-magnetic local time: ILAT-MLT) distributions. Since there were no direct comparisons of these in situ plasma measurements with highly resolving auroral images, as mentioned above, it is not obvious what types of auroral forms were associated with the electron signatures presented in these papers.…”
Section: Observations Of Auroral Arcs and Particlessupporting
confidence: 66%
“…Based on the Cluster observations, Sadeghi et al (2011) reported the characteristics found in the energytime (E-t) spectrograms and field-aligned current distributions obtained in neighboring potential structures. Park et al (2014) also showed similar properties of monoenergetic and broadband auroral electron components observed by the Science and Technology Satellite-I in addition to their electron energy distributions and statistical results on the basic parameters (characteristic energy, energy flux, pitch angle, temperature, and density) and spatial (invariant latitude-magnetic local time: ILAT-MLT) distributions. Since there were no direct comparisons of these in situ plasma measurements with highly resolving auroral images, as mentioned above, it is not obvious what types of auroral forms were associated with the electron signatures presented in these papers.…”
Section: Observations Of Auroral Arcs and Particlessupporting
confidence: 66%
“…The isotropic assumption is acceptable for the inverted‐V electron precipitation (Paschmann et al., 2002; J. Park et al., 2014). The other method estimates j ∥ based on the measurement of the cross‐track magnetic field perturbation (Δ B z ) by DMSP SSM with the assumption that the current sheets are infinitely long and perpendicular to the satellite track: j(normalB)=1μ0vnormalΔBnormalznormalΔt, where μ 0 is the vacuum permeability, v the satellite velocity, and Δ t a time step of 5 s in our case.…”
Section: Methodsmentioning
confidence: 99%
“…where J N,e is the electron number flux integrated over all the energy channels measured by SSJ/5. The isotropic assumption is acceptable for the inverted-V electron precipitation (Paschmann et al, 2002;J. Park et al, 2014).…”
Section: Current-voltage Relationmentioning
confidence: 99%